Pengaruhmotivasi, Komunkasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan Studi Pada Kantor Dinas Perdagangan Kabupaten Grobogan - Handoko, Sebrina Gandhy, Drs. Agus Muqorrobin, MM (2016)
The research titled effect of motivation, communication, and work environment on performance employees in trade office Grobogan district. The purpose of the study is to determine the effect of motivation, communication, and work environment on performance employees in trade office of Grobogan district. Methods of data collection in this research using primary and secondary data sources. The sampling method is done by employees taking technique taken half of the number of employees in the trade office of Grobogan. Because the number of relatively large populationn and with the aim to facilitate research. Total population of 100 people and the sample as many as 50 employees. The results showed that the regression test of motivation variable count value T (X 1) as big as 2,483, communication ( X2 ) as big as 2,097, work environment (X 3) as big as 2,105. So that the value has a value T count > T table that is > 2,002. Results F arithmetic calculation obtained a value of 22,453 and F table as big as 2,79. Then the F value of 22,453 > 2,79. That there is a positive and significant influence between the variable of motivation (X1), communication (X2), work environment (X3) conducted on employee performance (Y) office of trade Grobogan and the coefficient of determination (R2) by showing R2 = 0,568 that is motivation (X1), communication (X2), work environment (X3) can explain the performance of employees (Y) as big as 56,8 % the rest 43,2 % influenced by other variables not included in this model.